Depositional constraints from detrital zircon geochronology of strata from multiple lithotectonic belts in south-central Maine, USA - Cartwright, Samuel F.A.; West, Jr., David P.; Amidon, William H. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2019)
The bedrock geology of south-central Maine is characterized by a series of fault-bounded lithotectonic terranes that were accreted onto the Laurentian margin during Silurian-Devonian orogenesis.  The multiple phases of deformation and metamorphism associated with this tectonism obscured most primary features in the protolith rocks, leading to uncertainties in their pre-accretionary history. Here we present the results of detrital zircon geochronology from five of these terranes and make interpretations on their depositional ages, sediment provenance, and tectonic setting of deposition. Detrital zircon from Silurian rocks of the Vassalboro Group in the eastern-most portion of the Central Maine basin indicate sediment input in an extensional setting from both Laurentian and Ordovician sources.  Results from Ordovician rocks of the Casco Bay Group of the Liberty-Orrington belt support earlier findings that these rocks have strong peri-Gondwanan affinities.  Detrital zircon from the Appleton Ridge Formation and Ghent phyllite of the Fredericton trough are consistent with a peri-Gondwanan sediment source with no evidence of Laurentian sediment input.  These findings are consistent with that of Dokken et al. (2018) for older Fredericton trough strata (i.e., Digdeguash Formation) east of the Fredericton fault in southern New Brunswick.  Two samples from the Jam Brook complex reveal extreme differences in depositional age (Ordovician vs. Mesoproterozoic) and tectonic affinity and support the hypothesis that this narrow belt represents a fault complex containing a wide variety of stratigraphic units.  Detrital zircon from Ordovician rocks of the Benner Hill Sequence indicate a peri-Gondwanan sediment source with no Laurentian input. Collectively, the pre-Silurian rocks of the Liberty-Orrington belt, Jam Brook complex, Benner Hill Sequence, and Late Ordovician-Early Silurian strata from the Appleton Ridge and Ghent phyllite in the Fredericton trough show peri-Gondwanan affinities with no evidence of Laurentian sediment input.  This suggests a barrier exisited between the Laurentian margin and these peri-Gondwanan terranes prior to about 435 Ma.  In contrast, Silurian strata from the eastern portion of the Central Maine basin do show evidence of a Laurentian sediment source, along with deposition in an extensional setting (lacking in all other samples), thus signaling a fundamental change in tectonic regime.